Personality Disorders and Long-Term Sick Leave: A Population-Based Study of Young Adult Norwegian Twins. (14th January 2014) - Gjerde, Line C.; Røysamb, Espen; Czajkowski, Nikolai; Knudsen, Gun Peggy; Østby, Kristian; Tambs, Kristian; Kendler, Kenneth S.; Reichborn-Kjennerud, Ted; Ørstavik, Ragnhild E.
Abstract : Personality disorders (PDs) reduce global functioning, are associated with high levels of work disability, and are thus also likely to influence long-term sick leave (LTSL). Previous research has indicated significant genetic influence on both DSM-IV PDs and LTSL. To what degree genes contributing to PDs also influence LTSL has not been investigated. The aims of the current study were to investigate which PDs were significantly associated with LTSL, to what extent the genetic contributions to these PDs account for the heritability of LTSL, and to explore the hypothesis of a causal association between PDs and LTSL. The sample consisted of 2, 771 young, adult Norwegian twins, born 1967–1979. PDs were assessed using the Structured Interview for DSM-IV Personality (SIDP-IV). The age range for the interview was 20–32. The data were subsequently linked to public records of LTSL (sick leave >16 days) up to 11 years later. The odds ratio for being in the highest LTSL category (>15% sick leave) when fulfilling the DSM-IV criteria for any PD diagnosis was 2.6 (1.8–3.8, 95% CI). Dimensional representations of schizotypal, paranoid, and borderline PD were independently and significantly associated with LTSL. The heritability of LTSL was 0.50. Genetic factors shared with the PDs accounted for 20% of this. The association between PDs and LTSL was due to shared genetic and not environmental influences, and was mainly explained by one common genetic factor. The hypothesis of a causal association was not supported, indicating that the association is explained by overlapping genetic liability between PDs and LTSL.